2005
DOI: 10.1007/s10689-004-7992-1
|View full text |Cite
|
Sign up to set email alerts
|

Informing one’s family about genetic testing for hereditary non-polyposis colorectal cancer (HNPCC): a retrospective exploratory study

Abstract: Disclosure was stimulated if people felt morally obliged to do so or when they anticipated regret if something happened because it is preventable. Motivation to disclose seemed to increase if there were, especially fatal, cancer cases in the family. Presence of external cues (e.g. professionals) appeared important for disclosure as well. Disrupted and tense family relations were reasons not to disclose, as well as young age of the message recipients and negative experiences at their first attempt to disclose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 20 publications
1
68
0
Order By: Relevance
“…As was identified in our study, individual experiences of learning about heredity may also affect subsequent disclosure patterns (Forrest et al, 2003). Also, tense family relations and negative experiences from attempts to disclose information, may serve as barriers for information spread (Mesters et al, 2005). Hence, assimilation of genetic knowledge in the family is related to family …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…As was identified in our study, individual experiences of learning about heredity may also affect subsequent disclosure patterns (Forrest et al, 2003). Also, tense family relations and negative experiences from attempts to disclose information, may serve as barriers for information spread (Mesters et al, 2005). Hence, assimilation of genetic knowledge in the family is related to family …”
Section: Discussionmentioning
confidence: 56%
“…Communication with families with hereditary cancer is complex, but the individual's certainty in relation to his/her own risk estimated influences the likelihood of informing others (Forrest et al, 2003) and was also demonstrated in our study. A Dutch interview study in HNPCC has suggested that motivation to disclose information increases when cancer cases, especially if fatal, have occurred within the family (Mesters et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…D'Agincourt Canning [14] reported that mothers and fathers found telling their own children more burdensome because of the guilt they felt about passing on a mutation. Participants in the study by Mesters et al [9] were considered to have an attitude described as 'tomorrow never comes' with regard to their children; there is no age at which parents stop wishing to protect their children from potentially distressing information. It is of note that the mothers not at personal risk were less concerned about the possible negative implications of being at genetic risk for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Most family members are, in principle, willing to disclose genetic information to relatives [5], motivated by a perceived sense of duty [6][7][8][9]; this duty however conflicts with a desire to protect relatives from potentially harmful and difficult information [10][11][12][13]. Individuals find that informing relatives imposes moral dilemmas as to whom, how, and when to tell, and that having to tell others presents a burden they had not anticipated at the time of testing [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation